DNA damage (8-OHdG) and telomere length in captive Psittacidae birds with different longevity - Domínguez-de-Barros, Angélica; Sifaoui, Inés; Dorta-Guerra, Roberto; Lorenzo-Morales, Jacob; Castro-Fuentes, Rafael; Córdoba-Lanús, Elizabeth (Frontiers in Veterinary Science, 2024)
Aging is a complex process influenced by internal and external factors. Oxidative stress damages DNA, leading to 8-Hydroxy-2' deoxyguanosine formation (8-OHdG). Telomere shortening is considered a biomarker of aging and oxidative stress may enhance its attrition. The ability to manage and repair oxidative stress varies among species and life histories. Avian species, such as Psittacidae birds, exhibit exceptional lifespans despite their physiological characteristics that might suggest otherwise. This study investigates 8-OHdG levels in serum samples from long-and short-lived birds of the order Psittaciformes, examining their relationship with telomere length and antioxidant capacity based on lifespan strategies. Among 43 individuals analyzed 26 belonged to the "long-lived species" group and 17 belonged to the "short-lived species" one. Relative telomere length (rTL) was measured in DNA isolated from whole blood by qPCR, and oxidative stress markers, such as Total Antioxidant Capacity (TAC) and 8-OHdG, were determined by spectrophotometry in serum samples. Long-lived birds had longer rTL than short-lived ones [1.308 ± 0.11 vs 0.565 ± 0.13, (p<0.001)]. On the contrary, short-lived birds showed more DNA damage than their counterparts [3.847 ± 0.351 vs 2.012 ± 0.308, respectively, (p<0.001)]. Old birds had shorter rTL than young ones, for both longevity groups (p<0.001). Although no correlation was found between 8-OHdG levels and age, nor 8-OHdG and telomere length, long-lived birds exhibited 75.42-unit increased TAC levels when increased 8-OHdG concentrations (p=0.046). These findings highlight distinct patterns of telomere length and oxidative stress influenced by lifespan strategies among avian longevity groups.